Pescadores tradicionais da vila da Barra do Superagui : desafios e conflitos. - Kriegel, Raoni (Universidade Federal de São Carlos, 2015)
This dissertation submits a socio-environmental diagnostic of fisher s traditional community from Superagui, located in Superagui National Park, northern coast so Paraná. It was highlighted through theoretical searching the environmental impacts caused by anthropic activities related to both biotic and abiotic resources extracting, disorganized occupation over coastal and marine zones. It was utilized participative methodologies, qualitative and quantitative semi-structured questionnaires as well as direct observation and informal reports on field research. The results obtained from this research reveals internal reports on field research. The results obtained from this research reveals internal conflicts around the group researched as a result of individualist behaviors, lack of engagement and cooperativism. All these factors obstruct the group organization of seeking the group researched as a result of individualist behaviors, lack of engagement and cooperatives’. All these factors obstruct group organization among the legal institutions responsible for the mosaic of conservation areas over Parana coastline. At the end of this research it is advocated that the Agroecology and organic production national project ( PLONAPO), with its directives, targets and objectives perfect fit in the current configurations of this territory which may be incorporated by the legal institution as a federal legislation, offering a new rural and local development model to the social actors. The results obtained prove the hypothesis there is a lack of integration of the legal institutions and internal group disputes where the social actors are unable to organize themselves and seek for collective actions. The lack of engagement and organization to the claiming for their territory was evidenced. These internal and external pressures are hidden due to the fishing decreasing on the expectation of the management plan implementation and the search for other activities which could generate tourism income.
Fishermen traditional village superagui bar : challenges and conflicts.
Keywords: Agroecologia; Parque nacional; Atores sociais; Agroecology; National park; Social actors; CIENCIAS AGRARIAS